Агроекологічні перспективи розвитку природного виробництва. - Кобець, Анатолій Степанович; Kobets, Anatoly; Харитонов, Микола Миколайович; Kharytonov, Mikola; Грицан, Юрій Іванович; Grytsan, Yu.; Жуков, О. В.; Zhukov, O. (Дніпровський державний аграрно-економічний університет, 2015)
Стверджується, що природне сільське господарство – це цілісна система управління агровиробництвом. Використання її дозволяє нівелювати дію природних факторів, що особливо важливо в умовах глобальних змін клімату. Доведено, що природне землеробство, зокрема відмова від мінеральних добрив і пестицидів, знижує уразливість аграрних підприємств; витрати на одержання продукції у разі неврожаю в екстремальних погодних умовах. Agricultural production is closely dependent on environmental condi-tions and the environmental situa-tion. The solution of balanced opera-tion is associated with the develop-ment of agro-ecosystems or increase efficiency through the restoration of ecological regulatory mechanisms, which is reflected in the concept of restoring the biotic potential of agro-ecosystems. However, the diversity of climatic, soil and landscapes con-ditions of agriculture is far from equal financial opportunities force you to become convinced about the feasibility of multi-variant develop-ment of agricultural enterprises. The solution to this situation can be the using of natural agricultural technol-ogies of managing. Ecological or natural agriculture is an integrated system of management of agricultur-al production, which improves the condition of agro-ecosystems, bio-logical cycles and soil biological activity. Due to the fact that in natu-ral farming uses only organic mate-rials (compost, vermiculture, biolog-ical plant protection products, etc) increases the amount of nutrients and moisture in the soil. Thus, using the system of natural farming give pos-sibility to minimize the influence of natural factors, which is especially important in the context of global climate change. Natural farming re-duces the vulnerability of agricultur-al enterprises. The refusal from the mineral fertilizers and pesticides leads to a significant reduction of costs for production, which reduces the risk of partial crop failure due to extreme weather conditions associat-ed with global climate change. Or-ganic farming can not be economi-cally inefficient, because farmers guided by natural principles, which are low-cost and require low energy consumption, recycling of nutrients, synergistic effects.
Agriecological prospects of nature agriculture development.
Keywords: природне агровиробництво; natural farming; зміна клімату; climate change; споживання енергії; energy consumption; переробка відходів сільського господарства; recycling of agricultural wastes